A PERFORMER’S INQUIRY INTO EXPRESSIVE QUALITIES IN LUAN KAI’S MY LOVE IS WAITING FOR YOU - Wang Xueying; Yap Jin Hin (Universitas Hamzanwadi, 2025)
Luan Kai's work has notably influenced contemporary Chinese music, contributing to the evolution of this genre within a global framework. His works are extensively performed in China and have achieved notable international recognition. Nevertheless, there is a scarcity of research focusing on the particular vocal techniques utilized, including modal interchange and extended interpretation that integrate Eastern and Western practices. A study is required to examine the execution of ornamental figures and expressive markings authentically, taking into account the integration of traditional Chinese and Western vocal practices. This study examines one of his well-known songs, 我的深情为你守候 (My love is waiting for you), which highlights his distinctive compositional style that integrates traditional Chinese musical elements with contemporary harmonies and orchestration techniques. This study is conducted based on practice-based research. This study aims to enhance the academic understanding of music performance concerning Luan Kai's